Republic of Lithuania : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2002)
This report on the Observance of Standards and Codes data module provides a review of Lithuania's data dissemination practices against the IMF's Special Data Dissemination Standard, complemented by an in-depth assessment of the quality of the national accounts, consumer price index, producer price index, government finance, monetary, and balance-of-payments statistics, using the IMF's Data Quality Assessment Framework. The quality of Lithuania's macroeconomic statistics has improved significantly. The authorities have also established a good track record of implementing recommendations of the past IMF technical assistance missions in the area of statistics.